ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL - Alfiansah, Saeful; Sutiarso, Sugeng (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This study was conducted with the primary aim of evaluating and deeply understanding students' abilities in solving mathematical problems, specifically focusing on Linear Equations and Inequalities with One Variable (SPLSV). A qualitative approach was chosen because it allows researchers to delve deeper into students' thought processes and how they approach given mathematical problems. Descriptive analysis was used to interpret data systematically and in detail, enabling researchers to identify specific patterns in test data and interviews. Adab Kesuma Bangsa Junior High School in Natar, South Lampung, was selected as the research site because it was considered representative of the student population being studied. A total of 32 students participated in this study, selected through Purposive Sampling method. The research instruments used included written tests and in-depth interviews. The main indicators focused on in this research were: (1) understanding of the problem, which measured how well students could identify and comprehend key elements of mathematical problems; (2) solution planning, which assessed students' ability to formulate effective strategies or steps to solve problems; (3) solution implementation, which observed to what extent students could apply their plans in practice and achieve correct solutions; and (4) re-evaluation, which evaluated students' ability to reflect on their processes and outcomes, identifying errors or areas for improvement. The research findings indicated that only a small proportion of students (21.5%) demonstrated high problem-solving abilities. Approximately 11.5% were at a moderate level, while the majority of students (67%) exhibited low problem-solving abilities. These findings provide valuable insights for educators and policymakers regarding the need for more effective educational interventions to enhance students' mathematical problem-solving abilities